Language usage during shared reading—family communication as implicit plurilingual family language policy - Anna Dillon; Kay Gallagher; Sumaya Saqr; Claudine Habak; Yahia AlRamamneh (Frontiers in Communication)
This brief research report explores the language choices of Emirati fathers when sharing reading with their young children, and discusses how implicit plurilingual family language policies may be expressed through these choices. Participants’ responses were shared via WhatsApp messages following on from workshops provided by the team which offered tips for sharing reading. Fathers’ reported language choices for communicating via shared reading prompted the authors to reflect on these practices and situate them within a larger discussion on plurilingualism and the ways in books may be shared within plurilingual homes. The language choices of Emirati fathers demonstrate a range of implicit family language policies. They allude to translanguaging and plurilingual practices, which become enacted policies within the home. With some children wishing to read in English, others wishing to read in Arabic, some fathers reading in Emirati Arabic and combinations of all of those languages and language varieties, and only a few of them reading the book in the language within which it was originally printed, it seems like a translanguaging stance is being taken for communication within homes, as plurilingual repertoires are being actively harnessed through this shared reading.